Perancangan Fixture Pada Proses Sekrap Dan Freis Untuk Memproduksi Komponen Poros Idler - Muhammad Ikhsan; Raflina Sonya Jayanti; Citra Tri Angelia; Roni Hardian Putra; Frastia Retha (Jurnal Optimasi Sistem Industri, 2010)
Idler shaft is the engine components that are often produced in the automotive field, the shaft serves to continue the effort together with the rotation. Making idler shaft through several machining processes such as lathes, sekrap, and Freis. At this time laporn designed tools to process and Freis sekrap in the production of idler shaft. The design of this tool using the clamping screw. Placed on the front clamping tools for process sekrap. Based on the results obtained, the time spent with the tools and shorter setup times smaller than that obtained without the tools, so the production cost by using the tools is greater than the production costs without the tools in this case the production shaft idler.